2023
DOI: 10.21037/jtd-22-1289
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence of safety and influence for lung cancer surgery under COVID-19 pandemic in Japan

Abstract: Background:The COVID-19 pandemic has affected the clinical practice of lung cancer surgery in Japan, but few studies have revealed the real situation of surgical practice for lung cancer in this country. This latest information will help us to decide the future direction of lung cancer surgery under pandemic circumstances. Methods:We collected data from patients with primary lung cancer who underwent thoracic surgery between 2018 and 2021. To investigate the impact of the COVID-19 pandemic on lung cancer surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Regarding age and place of origin, no significant differences were reported among the three periods. These results are consistent with the literature, where in most studies, these variables did not significantly change throughout the pandemic [ 17 , 19 , 24 , 27 , 28 , 29 , 30 ]. However, Kirk et al [ 18 ] identified that patients undergoing surgery during the pandemic exhibited significantly higher ages ( p = 0.006) compared to the pre-pandemic period.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding age and place of origin, no significant differences were reported among the three periods. These results are consistent with the literature, where in most studies, these variables did not significantly change throughout the pandemic [ 17 , 19 , 24 , 27 , 28 , 29 , 30 ]. However, Kirk et al [ 18 ] identified that patients undergoing surgery during the pandemic exhibited significantly higher ages ( p = 0.006) compared to the pre-pandemic period.…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in the number of surgeries has been reported globally, with a hospital in the US also reporting a decrease of 50.4% compared to the previous period [ 17 ]. Significant differences have been evidenced in Queensland [ 18 ], as well as in countries such as Japan [ 19 ], Sweden [ 20 ], or England [ 21 ], where a significant decline in the number of surgical interventions performed has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Enlargement of primary lesions and progression of cancers discovered during the COVID-19 epidemic have been confirmed (15)(16)(17)(18)(19)(20)(21)(22). In breast cancer, for example, an increase in tumor size (15)(16)(17)(18)(19) and the of patients with advanced stage (17)(18)(19) has been reported.…”
Section: Discussionmentioning
confidence: 84%
“…In breast cancer, for example, an increase in tumor size (15)(16)(17)(18)(19) and the of patients with advanced stage (17)(18)(19) has been reported. In patients with resectable NSCLC, there were some reports of increased primary tumor diameter during the COVID-19 pandemic, although no differences were found in clinical stage (20)(21)(22). To our best knowledge, however, no study has assessed tumor size in advanced NSCLC during the COVID-19 pandemic and confirmed that they were diagnosed with greater size.…”
Section: Discussionmentioning
confidence: 93%
“…There were many difficult decisions that were made related to which types of surgeries were considered elective versus more urgent. The authors of the current study by Kato and colleagues described their experience during the pandemic and their outcomes in patients undergoing pulmonary resection for stage I lung cancers ( 1 ). In this editorial, we will review the current study and then give potential guidelines for future events.…”
Section: Introductionmentioning
confidence: 99%